Transparent collaboration between industry and academia can serve unmet patient need and contribute to reproductive public health - D'Hooghe, Thomas (Hum Reprod, 2017)
The pharmaceutical and device industry has greatly contributed to diagnostic and therapeutic approaches in reproductive medicine in a very highly regulated environment, ensuring that development and manufacturing follow the highest standards. In spite of these achievements, collaboration between industry and physicians/academia is often presented in a negative context. However, today more than ever, partnership between industry and academia is needed to shorten the timeline between innovation and application, and to achieve faster access to better diagnostics, drugs and devices for the benefit of patients and society, based on complementary knowledge, skills and expertise. Such partnerships can include joined preclinical/clinical and post-marketing research and development, joint intellectual property, and joint revenue. In Europe, the transparency of this collaboration between pharmaceutical industry and medical doctors has been made possible by the Compliance and Disclosure Policy published by the European Federation of Pharmaceutical Industries and Associations (EFPIA), which represents the major pharmaceutical companies operating in Europe, and includes as members some but not all companies active in infertility and women's health. Under the EFPIA Disclosure Code of conduct, companies need to disclose transfers of value including amounts, activity type and the names of the recipient Health Care Professionals and Organizations. EFPIA member companies have also implemented very strict internal quality control processes and procedures in the design, statistical analysis, reporting, publication and communication of clinical research, according to Good Clinical Practice and other regulations, and are regularly inspected by competent authorities such as the US Food and Drug Administration (FDA) or European Medicines Agency (EMA) for all trials used in marketing authorization applications. The risk of scientific bias exists not only in the pharmaceutical industry but also in the academic world. When academics believe in a hypothesis, they may build their case by emphasizing the arguments supporting their case, and either refute, refuse, oppose or ignore arguments that challenge their assumptions. A possible solution to reduce this bias is international consensus on study design, data collection, statistical analysis and reporting of outcomes, especially in the area of personalized reproductive medicine, e.g. to demonstrate superiority or non-inferiority of personalized ovarian stimulation using biomarkers. Equally important is that declarations of interest are reported transparently and completely in scientific abstracts and publications, and that ghost authorship is replaced by proactive and clear co-authorship for experts from industry where such co-authorship is required based on the prevailing ICMJE criteria. In that context, however, reviewers should stop believing that publications by industry authors only, or by mixed groups of co-authors from industry and academia, are more prone to bias than papers from academic groups only. Instead, the scientific quality of the work should be the only relevant criterion for acceptance of papers or abstracts, regardless of the environment where the work was done. In the end, neutrality does not exist and different beliefs and biases exist within and between healthcare professionals and organizations and pharmaceutical industries. The challenge is to be transparent about this reality at all times, and to behave in an informed, balanced and ethical way as medical and scientific experts, taking into account compliance and legal regulations of both industry and academic employers, in the best interest of patients and society.